The Superselective β1-Blocker Landiolol Enhances Inotropy of Endogenous and Exogenous Catecholamines in Acute Heart Failure - Feuerstein, Thomas J.; Krumpl, Günther (Cardiology and Cardiovascular Medicine, 2022)
β1-Adrenoceptors (β1-AR) blocker are an established therapy for the treatment of chronic left ventricular dysfunction. In the acute setting, however, the administration in patients with left ventricular failure is seen controversial, specifically as a potential negative inotropic effect and antagonism of the applied inotropic agents may possibly worsen the clinical situation of the patient. Recently the super selective short acting β1-AR Landiolol has been used in patients with acute left ventricular decompensation and, in conjunction with inotropic agents, did not deteriorate but improved the cardiovascular status of the patients. The present work summarizes the theories how a β1-AR blocker may act additive to inotropic agents in patients with acute cardiac failure. Specifically, receptor bindings models are presented in which the β1-AR blocker Landiolol can induce a positive inotropic response. These models are based on the fact that in patients with left ventricular dysfunction the plasma levels of catecholamines exceed their dissociation constants and rather decrease than improve the inotropic response due to negative cooperativity at the occupied receptor dimers. Low distinct Landiolol concentrations then reduce the negative cooperation and shift the receptor response curve into a more positive inotropic range. This article may thus help to minimise the reservations to the treatment of acute left ventricular deterioration with the super selective beta blocker Landiolol and positive inotropic agents. More so as the dose range calculated for Landiolol in these models and the one’s used in the intensive care setting prove to be identical.